Effect of magnetic nanoparticles with various geometrical shapes on morphology and dielectric properties of nanodispersions of nematic liquid crystal in polymer matrix - Kopčansky, P.; Timko, M.; Mitrova, Z.; Zavisova, V.; Koneracka, M.; Tomašovičova, N.; Tomčo, L.; Kovalchuk, O.V.; Bykov, V.M.; Kovalchuk, T.M.; Lad, A.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Prepared in this work are dispersions of nematic liquid crystal in polyvinyl
alcohol with sizes of liquid phase inclusions less than one micrometer (nano-polymer
dispersed liquid crystal (PDLC)) by changing technology of mixing the components. It
was shown that, like to the case of earlier examined dispersions with the droplet sizes 6
to 10 μm (micro-PDLC), the conductivity of nano-PDLC has two components: the ion
one, which value does not depend on frequency, and the electron one, the value of which
depends on frequency according to a power law. It was found that the ion conductivity of
nano-PDLC is three orders of magnitude higher than that for micro-PDLC, and the
exponent for the electron components of nano-PDLC conductivity is less than that for
micro-PDLC. It was shown that the spherical and rod-like magnetic nanoparticles (MNs)
influence in a different manner on the conductivity components of nano-PDLC. If for the
maximum concentration of spherical MNs 2 * 10⁻³ wt.% the ion conductivity is 2-fold
increased, then at the same concentration of rod-like MNs the ion conductivity value
increases by more than one order of magnitude